Photovoice and Being Intentional About Empowerment. Issue 2 (March 2022) - Liebenberg, Linda
The intent of Photovoice is to produce research in collaboration with communities, ensuring that research is relevant to community needs and critically facilitates change required to address these needs. Accordingly, Photovoice extends research for knowledge production, emphasizing research for social change. Consequently, Photovoice stands to make an important contribution to relevant and impactful knowledge production with health promotion research. However, if the intent of Photovoice as reflected in its theoretical underpinnings is not accounted for from the outset, the value of the approach may not be fully realized. This article considers what the theoretical underpinnings of Photovoice are, how this relates to issues of power and empowerment theory, and how voice can be better ensured within a process that is intentional about empowerment and representation.